Sugarcane Plant Nutrient Diagnosis - J. Mabry McCray; Ike V. Ezenwa; Ronald W. Rice; Timothy A. Lang (EDIS, 2006)
SC075, a 25-page fact sheet by J. Mabry McCray, Ike V. Ezenwa, Ronald W. Rice and Timothy A. Lang, describes how growers can use leaf nutrient analysis in combination with visual evaluation of malnutrition symptoms to complement a consistent soil testing program and make improved decisions regarding fertilization. Includes references, table of sugarcane leaf nutrient critical values and optimum ranges, and 43 color figures to assist with field identification of nutritional problems. Published by the UF Agronomy Department, July 2006.